Total neoadjuvant therapy in rectal cancer: the evidence and expectations - Boublikova, Ludmila; Novakova, Alena; Simsa, Jaromir; Lohynska, Radka (Critical reviews in oncology/hematology, 2023)
Current management of locally advanced rectal cancer achieves high cure rates, distant metastatic spread being the main cause of patients' death. Total neoadjuvant therapy (TNT) employs (chemo)radiotherapy and combined chemotherapy prior to surgery to improve the treatment outcomes. TNT has been shown to reduce significantly distant metastases, increase disease-free survival by 5 - 10% in 3 years, and finally also overall survival (≈ 5% in 7 years). It proved to double the rate of pathologic complete responses, making it an attractive strategy for non-operative management to avoid permanent colostomy in patients with distal tumors. In addition, it endorses adherence to the therapy due to better tolerance and, potentially, shortens its overall duration. A number of questions related to TNT remain currently unresolved including the indications, preferred radiotherapy and chemotherapy regimens, their sequence, timing of surgery, and role of adjuvant therapy. A stratified approach may be the optimal way to go.
Keywords: Neoadjuvant Therapy; kombinovaná terapie; protokoly protinádorové kombinované chemoterapie; neoadjuvantní terapie; chemoradioterapie; staging nádorů; Humans; Rectal Neoplasms; Combined Modality Therapy; Motivation; Neoplasm Staging; motivace; lidé; Chemoradiotherapy; Antineoplastic Combined Chemotherapy Protocols; nádory rekta